Choose your collaborators wisely: Addressing interdependent tasks through collaboration in responding to wildfire disasters - Bodin, Örjan (Stockholm University, 2022)
The study applies a network-centric method to investigate wildfire responder networks in Canada and Sweden. It investigates actor collaboration when addressing interdependent tasks, and assesses how certain network structures of actors-and-tasks relationships influence task effectiveness.

The published article describes the data in-depth. The data consists of collaborative relationships between the actors that participated in the wildfire responses, and the actors' assessments of their own effectiveness in addressing their tasks. The data has been analysed in order to evaluate if and how the collaborative relationships have effected the actors' effectiveness in addressing their tasks. The method is thoroughly described in the article. An R script made available together with the data files also described the analyses.

Studien tillämpar ett nätverksperspektiv för att undersöka samverkan i hanteringen av två skogsbränder i Sverige och Kanada. Syftet är att förklara hur samverkan i de fall aktörerna arbetar med ömsesidigt beroende delproblem påverkar deras förmåga att hantera delproblemen på ett effektivt sätt.

Den publicerade artikeln beskriver utförligt datan, som består av samarbetsrelationer mellan aktörer som deltagit i skogsbrandsbekämpning, samt deras egen uppskattning om hur effektivt de löste sina uppgifter. Denna data har sedan analyserats för att utröna om och hur relationerna kan ha påverkat deras effektivitet. Metoden beskrivs utförligt i artikeln. Ett R script som finns tillgängligt i datafilerna beskriver också de genomförda analyserna.
Välj vilka du samverkar med på ett klokt sätt: Att genom samverkan hantera ömsesidigt beroende delproblem i hanteringen av skogsbränder
Keywords: social networks; socialt nätverk; Wildfires; Skogsbränder; Government, political systems and organisations; Regering, politiska system och organisationer; Public Administration Studies; Studier av offentlig förvaltning